A three-year follow-up of congenital adrenal hyperplasia newborn screening - Isabela L. Pezzuti; Cristina B. Barra; Rafael M. Mantovani; José N. Januário; Ivani N. Silva (Brazilian Society of Pediatrics, 2014)
Objective: congenital adrenal hyperplasia (CAH) newborn screening can prevent neonatal mortality in children with the salt-wasting form of the disease and prevent incorrect gender assignments, which can occur in females. However, the occurrence of false-positive results in preterm or low-birth-weight newborns creates some diagnostic difficulties, with consequent therapeutic implications. This study aimed to report the results of a pilot project for neonatal CAH screening conducted in the state of Minas Gerais, Brazil from 09/2007 to 05/2008 with a three-year follow-up. Methods: dried blood specimens were collected on filter paper cards three to seven days after birth of all newborns in the period. Samples were analyzed for 17-hydroxyprogesterone using an enzyme-linked immunosorbent assay (ELISA). Results: a total of 159,415 children were screened. The apparent incidence of the classic variant of the disease was 1:9,963, based on initial diagnoses following newborn screening. During the follow-up period, eight of 16 children initially diagnosed with CAH were reclassified as unaffected, resulting in a revised incidence of 1:19,927. The false-positive rate was 0.31%, and the positive predictive value was 2.1%. Sensitivity and specificity were 100% and 99.7%, respectively. Conclusions: newborn screening is an important public health policy in developing countries such as Brazil, where CAH remains underdiagnosed. It has great potential to identify children with the disease who otherwise cannot be diagnosed earlier. Long-term follow-up and monitoring of all children with positive screening results are crucial to ensure a correct diagnosis and to calculate a reliable incidence ratio of the disease.